METABOLIC SYNDROME AND PROGESSION OF CHRONIC KIDNEY DISEASE : A SYSTEMATIC REVIEW - Talilah, Stephanie (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Indicators of metabolic function, cardiovascular health, and inflammation are all components of the metabolic syndrome, which is a cluster of risk factors. The metabolic syndrome is defined and characterized in a variety of different ways, depending on who you ask. Individuals are considered to have metabolic syndrome (MetS) when multiple risk factors for chronic kidney disease, such as obesity, hyperglycemia, hypertension, and dyslipidemia (high triglyceride and low HDL-C), co-occur within the same person. These risk factors include high triglyceride levels and low HDL-C levels. A high level of triglycerides and a low level of HDL-C are two of these risk factors. A mechanistic explanation for MetS as a cause of CKD would be more convincing than simply stating that the two conditions are connected. Research is absolutely necessary if "black boxes" are to be removed from any postulated chain of causality connecting metabolic syndrome and chronic kidney disease. It has been demonstrated that metabolic syndrome is a risk factor for a number of chronic diseases that are not contagious, some of which are diabetes type 2, coronary heart disease, stroke, and chronic kidney disease. According to the information that we have, hypertension is the factor that contributes to metabolic syndrome more frequently than any other, which leads to CKD.